Implementasi SDM Melalui Program Sekolah Penggerak Dalam Pengembangan Guru Dan Keterlibatan Masyarakat - Windiasari, Kikik; Rahmatillah, Alda Novita; Rusdiah, Nadira; Agus R, Abu Hasan; Ani, Emi Dwi; Maryanto, Maryanto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the implementation of the Sekolah Penggerak program at SMA Negeri 1 Besuki with a focus on developing teacher human resources (HR) and community involvement in supporting the quality of education. Using a qualitative approach with a case study method, this study collected data through in-depth interviews, observations, and documentation from the principal, teachers, and the community. The results showed that the Sekolah Penggerak program had a significant impact on improving teacher pedagogical competence and professionalism. Most teachers participated in ongoing training that included curriculum development, educational technology, leadership, and classroom management. This training helped teachers integrate innovative and technology-based learning methods, thereby improving the quality of teaching and student learning outcomes. In addition, community involvement, especially parents of students, played an active role in supporting school activities, both through moral and material contributions, and participation in the School Committee. Community participation created collaborative relationships that strengthened the education ecosystem at SMA Negeri 1 Besuki. The Sekolah Penggerak program at SMA Negeri 1 Besuki also encouraged project-based learning and student character development through extracurricular activities and integration of local values. This holistic approach had a positive impact on the quality of education that was more inclusive, innovative, and relevant to the needs of the community.